The influence of identity-oriented psychotrauma therapy on Hashimoto disease activity: a randomised controlled trial - Maria-Magdalena Macarenco; Cristian Opariuc-Dan; Teodora Georgescu (European Journal of Psychotraumatology)
Background: Childhood adversity and trauma have been linked to altered thyroid function and hypothyroidism, yet few randomised controlled trials (RCTs) have examined the effectiveness of trauma-focused psychological interventions in patients with Hashimoto’s thyroiditis (HT).Objective: This study aimed to evaluate the effectiveness of Identity-Oriented Psychotrauma Therapy (IOPT) in adults with HT, focusing on both immunological and psychological outcomes.Method: This parallel-group RCT randomised 70 adults with HT (93.94% women; age 25–57) to receive treatment as usual (TAU) or TAU plus IOPT. The intervention comprised 10 bimonthly group sessions, one session every two weeks. Outcomes included thyroid peroxidase (TPO-ab) and thyroglobulin (TG-ab) antibodies, along with depression, anxiety, stress, dissociation, alexithymia, and anger, assessed at baseline, post-treatment, and 3-month follow-up. A series of 2-way mixed-model ANOVAs and Bonferroni-corrected post-hoc tests were used. Missing data due to attrition – particularly in the control group (37%) – were addressed via multiple imputation, and sensitivity analyses were conducted to test robustness.Results: Initial analyses suggested that IOPT significantly reduced TPO-ab levels compared to TAU (p < .001), with effects maintained at follow-up (p = .01); however, these effects were not replicated in complete case analysis. IOPT led to significant improvements in dissociation (p = .03), alexithymia (p < .001), depression (p < .001), anxiety (p < .001), stress (p = .015), state anger (p = .009), anger-in (p = .009), and quality of life (p = .042) at follow-up.Conclusion: These preliminary findings suggest that IOPT, when added to standard medical care, may offer psychological benefits for HT patients and could potentially influence immunological outcomes. However, given the attrition-related sensitivity of some results, further replication in larger, well-retained samples is necessary before drawing definitive conclusions.Trial registration: ClinicalTrials.gov identifier: NCT04600349.